SURGICAL TREATMENT OF COMPLICATIONS OF THE ELBOW JOINT WITH THE HELP OF A CHARTERED - DISTRACTIVE VOLKOV – OGANESYAN APPARATUS (World Bulletin of Public Health, 2023)
Traumatology and orthopedics are now referred to by scientists in the current boskich, the treatment of injuries in the area of the elbow bygimi. Treatment of post-surgical complication of the elbow joint is a serious and unresolved problem, including contracture, outdated exit, ankylosis, and now the results of its treatment will satisfy neither the doctor nor the patient. Complications in the elbow joint are 20.5 -82% g. The reason for this is the dynamic apparatus of the elbow joint, the variety of operating costs. Any dislocation in the elbow joint has an effect on its fuction, since the joint is "super sensitive" .